Lithium metal battery

By using high-nickel ternary materials and specific electrolytes in lithium metal batteries, combined with flame retardant additives, the problem of difficulty in taking into account low-temperature cycling performance and safety performance when improving energy density is solved, and a more stable and safe battery performance is achieved.

CN119695236APending Publication Date: 2025-03-25ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411904858.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

While existing lithium metal batteries increase the battery energy density, it is difficult to take into account both low-temperature cycle performance and overcharge safety performance.

Method used

High nickel ternary material is used as the positive electrode material, and a specific content of the first ether solvent, the second ether solvent (1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether) and lithium bisfluorosulfonimide are added to the electrolyte to improve battery performance.

Benefits of technology

While ensuring high energy density, the low-temperature cycle stability and safety of the battery are significantly improved, reducing the risk of lithium dendrites and thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695236A_ABST
    Figure CN119695236A_ABST
Patent Text Reader

Abstract

The invention relates to the field of battery materials, and discloses a lithium metal battery. The invention provides a lithium metal battery. The lithium metal battery comprises a positive plate, a negative plate and electrolyte, the positive plate comprises a high-nickel ternary material; the electrolyte comprises a first ether solvent, a second ether solvent and lithium bis (fluorosulfonyl) imide; the oxygen content of the first ether solvent is A'wt%, and A 'is greater than or equal to 18; the first ether solvent is 1, 1, 2, 2-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether, and the second ether solvent is 1, 1, 2, 2-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether; the mass ratio of the 1, 1, 2, 2-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether in the electrolyte is Bwt%, and the mass ratio of the 1, 1, 2, 2-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether in the electrolyte is 9-65%. By comprehensively regulating and controlling the mass ratio of the first ether solvent with high oxygen content, the 1, 1, 2, 2-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether and the lithium bis (fluorosulfonyl) imide in the electrolyte, the safety and the low-temperature cycle stability can be obviously improved under the condition of effectively ensuring the high energy density of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery materials, and in particular to a lithium metal battery. Background Art

[0002] As people pursue high energy density, lithium metal has become an ideal negative electrode material due to its extremely high theoretical energy density (3860mAh / g) and low electrochemical potential (-3.040V relative to the standard hydrogen electrode), which can significantly improve the energy density of the battery. However, during the charging and discharging process of lithium metal, due to volume expansion and contraction, some lithium metal may lose its electrochemical activity, forming the so-called "dead lithium", which reduces the cycle stability and energy efficiency of the battery; and during the charging and discharging process of lithium metal, especially in the case of overcharging, lithium metal will precipitate on the negative electrode surface and form lithium dendrites in an uneven deposition on the lithium metal negative electrode, which not only reduces the coulomb efficiency of the battery, but the formed lithium dendrites may also penetrate the diaphragm, causing internal short circuits, and then leading to thermal runaway, further threatening the safety of the battery and causing safety accidents.

[0003] Moreover, existing liquid electrolytes conventionally use carbonates, which are easily reacted with lithium metal, have poor compatibility with lithium metal negative electrodes, and have many side reactions, forming an unstable solid electrolyte interface (SEI) on the negative electrode surface, leading to battery performance degradation and poor cycle stability, especially poor low-temperature cycle stability. Summary of the invention

[0004] The present application provides a lithium metal battery, which aims to solve to a certain extent the problem that the existing lithium metal battery cannot take into account both low-temperature cycle performance and overcharge safety performance while increasing the battery capacity.

[0005] The present application provides a lithium metal battery, including a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0006] The positive electrode sheet includes a high-nickel ternary material;

[0007] The electrolyte includes a first ether solvent, a second ether solvent and lithium bis(fluorosulfonyl)imide; the oxygen content of the first ether solvent is A'wt%, A'≥18; the second ether solvent is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether;

[0008] The mass proportion of the 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether in the electrolyte is Bwt%, and B is 9-65.

[0009] The structural formula of the first ether solvent is shown in Formula 1,

[0010] Formula 1: Wherein, R1 and R2 are each independently selected from one or more of halogen, substituted or unsubstituted alkyl or ether group having 1 to 5 carbon atoms, substituted or unsubstituted carboxylate group having 2 to 5 carbon atoms, substituted or unsubstituted sulfonate group having 1 to 5 carbon atoms, substituted or unsubstituted sulfate group having 1 to 5 carbon atoms, and the total number of oxygen atoms in R1 and R2 is greater than or equal to 2.

[0011] Preferably, the first ether solvent comprises at least one of the following structural formulas 1-1 to 1-8:

[0012]

[0013] The mass proportion of the first ether solvent in the electrolyte is Awt%, wherein A is 15-50.

[0014] And / or, the mass proportion of the lithium bis(fluorosulfonyl)imide in the electrolyte is Cwt%, and C is 20-40;

[0015] Preferably, A+B+C≥80.

[0016] The electrolyte further includes a flame retardant additive, wherein the flame retardant additive includes a phosphorus-containing compound, for example, at least one of phosphazene and fluorophosphate;

[0017] Preferably, the phosphorus-containing compound includes tris(2,2,2-trifluoroethyl) phosphate, ethoxy(pentafluoro)cyclotriphosphazene (PFPN), p-toluoyl phosphate, trimethyl phosphate, ethyl hexafluorophosphate, propyl pentafluorophosphate, di(2,2,2-trifluoroethyl) carbonate, hexafluorocyclotriphosphazene, tricyanophosphate, tris(trimethylsilane) phosphate, tris(trimethylsilane) phosphite.

[0018] Preferably, the added amount of the flame retardant additive is Fwt% of the mass of the electrolyte, and 0.2≤F≤20.

[0019] The high-nickel ternary material includes single crystal material and / or polycrystalline material;

[0020] Preferably, the mass percentage of the single crystal material to the high-nickel ternary material is D wt%, where D is 15-80, preferably 50-80.

[0021] 0.3≤B / D≤3, preferably, 0.4≤B / D≤1.8.

[0022] The high-nickel ternary material is further doped with a coating element, preferably, the coating element is one or more elements selected from the group consisting of Al, Zr, Mg, Y, Ti, B, Sr, W, Si, La, and Nb;

[0023] Preferably, the coating element includes at least one of Al, Mg and Zr;

[0024] Preferably, based on the high-nickel ternary material, the coating element content is 100-7000 ppm; preferably, the total mass of Al+Mg+Zr is 1000-7000 ppm of the high-nickel ternary material content.

[0025] The lithium metal battery is a laminated battery, the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes lithium metal.

[0026] The thickness of the negative electrode sheet is T1, the thickness of the positive electrode sheet is T2, the total thickness of the electrode sheets is T, T=T1+T2, 0.03≤A / T≤0.5, preferably, 0.1≤A / T≤0.4.

[0027] Range adjustment: 40μm≤T1≤210μm, 50μm≤T2≤210μm, 120μm≤T≤420μm.

[0028] The technical solution of this application has the following advantages:

[0029] A lithium metal battery provided by the present application includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet includes a high-nickel ternary material; the electrolyte includes a first ether solvent, a second ether solvent and lithium bis(fluorosulfonyl)imide, and the second ether solvent is limited to 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and the oxygen content of the first ether solvent is A'wt%, A'≥18; wherein the mass proportion of the second ether solvent in the electrolyte is Bwt%, and B is 9-65. The present invention can take into account low-temperature cycle stability and safety while ensuring high energy density by cooperating with the first ether solvent with a specific content of the second ether solvent and a specific oxygen content.

[0030] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0032] Figure 1 It is a SEM electron microscope image of the high nickel ternary material of the present invention.

[0033] The reference numerals are described as follows:

[0034] 1-single crystal particles, 2-polycrystalline particles. DETAILED DESCRIPTION

[0035] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0036] In the description of the present application, it should be noted that the terms "inside" and "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present application. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0037] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0038] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.

[0039] The present application provides a lithium metal battery, including a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0040] The positive electrode sheet includes a high-nickel ternary material;

[0041] The electrolyte includes a first ether solvent, a second ether solvent and lithium bis(fluorosulfonyl)imide, the second ether solvent is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and the oxygen content of the first ether solvent is A'wt%, A'≥18;

[0042] The mass proportion of the 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether in the electrolyte is Bwt%, and B is 9-65.

[0043] The energy density of the lithium metal battery in the present invention is higher than that of the lithium-ion battery. The overall energy density can be further improved by combining it with a high-nickel ternary material. However, the high nickel content will lead to instability in the structure of the positive electrode material and poor thermal stability. In addition, the interaction between the positive electrode and the lithium metal negative electrode will lead to more complex interface problems, exacerbating the thermal runaway problem of the lithium metal battery.

[0044] The high-nickel ternary material in the present invention refers to a ternary material in which the mass percentage of nickel element is more than 60%.

[0045] On the one hand, the present invention adds 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (F-EFPE) as the second ether solvent in the electrolyte, which is conducive to forming a good interface film on the positive electrode and the lithium metal negative electrode including the high nickel ternary material, and at the same time controls the oxygen content of the first ether solvent to be greater than or equal to 18%, improves the electrochemical window of the electrolyte, and can enhance the stability of the positive and negative electrode interface. Therefore, F-EFPE and the first ether solvent work together to improve the structure of the high nickel ternary material and the stability of the positive and negative electrode interface, inhibit the formation of lithium dendrites, and F-EFPE and the first ether solvent have good thermal stability, and can maintain the stability of the electrolyte at a higher temperature, thereby improving the thermal runaway problem of the lithium metal battery. On the other hand, F-EFPE and the first ether solvent can jointly reduce the viscosity of the electrolyte, further increase the content of lithium bis(fluorosulfonyl)imide (LiFSI) added to reduce the freezing point of the electrolyte, reduce the impedance at low temperature, and effectively improve the migration of lithium ions at low temperature, thereby improving the low temperature cycle performance of lithium metal. In summary, through the combined action of F-EFPE, the first ether solvent with a specific oxygen content and LiFSI, the low-temperature performance of the battery is significantly improved and the electrochemical stability and thermal safety of the battery are enhanced.

[0046] As an example, the mass proportion B% of the second ether solvent in the electrolyte can be 9%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or in the range of any two of the above values; the oxygen content A'% in the first ether solvent can be 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35% or in the range of any two of the above values.

[0047] In an optional embodiment, the structural formula of the first ether solvent is as shown in Formula 1,

[0048] Formula 1: Wherein, R1 and R2 are each independently selected from one or more of halogen, substituted or unsubstituted alkyl or ether group having 1 to 5 carbon atoms, substituted or unsubstituted carboxylate group having 2 to 5 carbon atoms, substituted or unsubstituted sulfonate group having 1 to 5 carbon atoms, substituted or unsubstituted sulfate group having 1 to 5 carbon atoms, and R1 and / or R2 contain at least one oxygen atom.

[0049] Preferably, the compound comprises at least one of the following structural formulas 1-1 to 1-8:

[0050]

[0051] When the first ether solvent further includes the above-mentioned structural formula, the uniformity, chemical stability and mechanical properties of the interface film can be improved, which helps to reduce the diffusion energy barrier of lithium ions, effectively inhibits the growth of lithium dendrites, promotes the uniform deposition of lithium, and can improve the cycle stability and thermal runaway safety of the battery.

[0052] Similarly, the mass proportion of the first ether solvent in the electrolyte is Awt%, and A is 15-50; when A is too low, it cannot be well matched with the second ether solvent, the growth of its lithium dendrites cannot be inhibited, and the low-temperature cycle performance and cycle life are poor; when A is too high, it will cause the second ether solvent (F-EFPE) and lithium bis(fluorosulfonyl)imide in the electrolyte to decrease in content, reduce oxidation resistance, and further affect the stability of the positive and negative electrode interface films, and affect the cycle performance, especially the low-temperature cycle performance; in summary, the present invention achieves the effect of improving the low-temperature performance of the battery by controlling A.

[0053] As a preferred embodiment, the mass proportion of the lithium bis(fluorosulfonyl)imide in the electrolyte is Cwt%, C is greater than 20, preferably 20-40; when the content of lithium bis(fluorosulfonyl)imide is too low, it affects the ionic conductivity and also causes the electrolyte to have poor wettability on the positive and negative electrode sheets, resulting in large internal resistance, thereby affecting the charge and discharge efficiency and energy density of the battery. Based on the requirements of energy density, the content C of lithium bis(fluorosulfonyl)imide is preferably greater than 20. Based on the dissolution of lithium salt in the electrolyte, the control of C in the present invention achieves both energy density and solubility performance.

[0054] As an example, the mass proportion A% of the first ether solvent in the electrolyte can be 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38%, 40%, 43%, 45%, 48%, 50% or in the range of any two of the above values; the mass proportion C% of LiFSI in the electrolyte can be 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38%, 40% or in the range of any two of the above values.

[0055] To further ensure the coordination effect between the first ether solvent, the second ether solvent and lithium bis(fluorosulfonyl)imide in the electrolyte, preferably, A+B+C≥80.

[0056] In an optional embodiment, the electrolyte also includes a flame retardant additive, and the flame retardant additive preferably includes a phosphorus-containing compound, for example: at least one of phosphazene and fluorophosphate; the flame retardant mechanism of phosphorus-containing compounds is mainly based on the phosphorus element in its molecular structure. The compound generated by the reaction when heated can form a protective film on the surface of the battery, reduce the contact between the battery and the air, and effectively prevent the occurrence of thermal runaway. Phosphate compounds decompose in the flame to produce phosphorus-containing free radicals, which combine with hydrogen radicals (H·) to inhibit combustion; the introduction of fluorine will also reduce the flammability of the electrolyte, and hydrogen radicals can be removed by forming fluorine free radicals. Therefore, the safety performance of lithium metal batteries can be further increased by adding flame retardant additives, especially phosphazenes and / or fluorophosphates; preferably, the amount of flame retardant additives added is Fwt% of the mass of the electrolyte, 0.2≤F≤20;

[0057] As an example, the flame retardant additive is selected from at least one of tris(2,2,2-trifluoroethyl) phosphate, ethoxy(pentafluoro)cyclotriphosphazene, p-toluoyl phosphate, trimethyl phosphate, ethyl hexafluorophosphate, propyl pentafluorophosphate, di(2,2,2-trifluoroethyl) carbonate, hexafluorocyclotriphosphazene, tris(trimethylsilane) phosphate, and tris(trimethylsilane) phosphite.

[0058] As an example, the addition amount of the flame retardant additive as F% of the electrolyte mass can be 0.2%, 3%, 5%, 7%, 10%, 13%, 15%, 18%, 20% or within the range of any two of the above values.

[0059] High nickel ternary materials are divided into single crystal materials and polycrystalline materials according to their crystal form, such as Figure 1 As shown, the high-nickel ternary material in the present invention can be a single crystal material, a polycrystalline material, or both. There is no grain boundary inside the single crystal material, which can effectively deal with the grain boundary crushing and the performance degradation caused by it. In order to ensure the cycle stability and safety of lithium metal, the present invention considers using single crystal materials as the main material, but too much single crystal material will lead to the problem of high cost, and the lithium ion diffusion rate of single crystal material is lower than that of polycrystalline material. By mixing polycrystalline material, the diffusion rate of lithium ions can be increased, thereby improving the low-temperature charge and discharge performance of the battery; therefore, the high-nickel ternary material in the present invention preferably adopts the method of mixing single crystal material and polycrystalline material.

[0060] In an optional embodiment, the mass proportion of single crystal material in high nickel ternary material is in the range of 15wt%≤D wt%≤80wt%, preferably 50wt%≤D wt%≤80wt%; high nickel ternary material works under high voltage, has poor chemical stability, is easy to have side reactions with electrolyte, cycle performance will deteriorate, and the risk of thermal runaway will also increase; in order to further improve the stability of the electrolyte, single crystal high nickel ternary material is required, and the content of single crystal high nickel ternary material should not be too low, otherwise it will not achieve the effect of improving cycle performance and reducing thermal runaway risk; but it should not be too high, otherwise it will lead to higher cost and low lithium ion diffusion rate, and during long-term cyclic use, the material may undergo chemical mechanical degradation, resulting in structural damage and decreased cycle performance; the present invention achieves the effect of improving cycle performance and reducing thermal runaway risk by controlling the mass proportion of single crystal material in high nickel ternary material.

[0061] As an example, the mass proportion D wt% of single crystal material in high nickel ternary material can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or in the range of any two of the above values.

[0062] In an optional embodiment, the present invention can comprehensively control the content Bwt% of F-EFPE and the mass proportion Dwt% of single crystal materials by controlling 0.3≤B / D≤3, thereby achieving better safety and cycle stability of the battery. Specifically, its implementation mechanism is: by increasing the mass proportion of single crystal materials to improve the stability of the electrolyte, but too high a mass proportion of single crystal materials will lead to a low lithium ion diffusion rate, and during long-term cyclic use, the material may undergo chemical mechanical degradation, resulting in structural damage and decreased cycle performance; and by increasing the content Bwt% of F-EFPE, the stability of the interface film formed between the positive and negative electrodes can be appropriately improved, and the viscosity of the electrolyte can be reduced, which is beneficial to the diffusion of lithium ions; if B / D is too low, the electrolyte stability is low, the stability of the interface film is poor, and the structure is easily destroyed, thereby affecting the safety performance and cycle performance; if B / D is too high, the mass proportion of single crystal materials is small, and the purpose of improving cycle performance and reducing the risk of thermal runaway cannot be achieved. Preferably, 0.4≤B / D≤1.8, within this range, better safety performance and cycle stability can be achieved.

[0063] As an example, the value of B / D may be 0.3, 0.4, 0.6, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.3, 2.5, 2.7, 3 or a range formed by any two of the above values.

[0064] In an optional embodiment, the high-nickel ternary material has poor stability under high voltage, and the risk of thermal runaway will also increase. The doping coating element can replace part of the transition metal atoms in the lattice of the high-nickel ternary material, thereby enhancing the structural stability of the lattice, inhibiting the migration of the Ni element, reducing the cation mixing, reducing the crystal structure fragmentation under overcharge conditions, and improving the conductivity of electrons and lithium ions. This structural reinforcement not only helps to inhibit the phase change and structural collapse of the material under high voltage or overcharge conditions, but also reduces the side reaction between the positive electrode material and the electrolyte, and reduces the risk of heat accumulation; the chemical stability and safety of the high-nickel ternary material are further improved by doping the coating element. That is, the high-nickel ternary material is also doped with a coating element, preferably, the coating element is one or more elements of Al, Zr, Mg, Y, Ti, B, Sr, W, Si, La, and Nb. More preferably, the coating element includes at least one of Al, Mg and Zr, wherein the total mass of the coating elements is 100-7000ppm of the high nickel ternary material content, and preferably the total mass of Al+Mg+Zr is 1000-7000ppm of the high nickel ternary material mass.

[0065] As an example, the total mass of Al+Mg+Zr is 100ppm, 500ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm of the mass of the high nickel ternary material or is within the range of any two of the above values.

[0066] In an optional embodiment, the lithium metal battery is a laminated battery; the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes lithium metal; the contact area between the laminated electrodes is larger, and the space can be effectively utilized, which helps to improve the charging and discharging efficiency and power density of the battery. The laminated structure can provide a more direct and continuous heat conduction path, which is conducive to heat dissipation, thereby preventing overheating and further ensuring the safety performance of the battery.

[0067] By increasing the thickness of the electrode, the load of the electrode active material can be increased, which can significantly improve the energy density of the battery. However, at the same time, the thickening of the electrode may increase the transmission distance of lithium ions inside the electrode, thereby reducing the ion diffusion rate, affecting the charge and discharge performance of the battery, and easily accumulating heat, reducing the safety performance; setting a suitable positive electrode thickness T1, negative electrode thickness T2, and total electrode thickness T = T1 + T2, that is, 40μm≤T1≤210μm, 50μm≤T2≤350μm, 120μm≤T≤420μm, can improve the thermal distribution of the battery during high-rate charge and discharge, reduce the risk of thermal runaway, enhance the mechanical stability of the battery structure, ensure high energy density while taking into account the comprehensive performance of cycle stability and safety.

[0068] As an example, a suitable positive electrode sheet thickness T1 may be 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 150 μm, 200 μm, 210 μm, or within a range formed by any two of the above values; a suitable negative electrode sheet thickness T2 may be 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 150 μm, 200 μm, 210 μm, or within a range formed by any two of the above values. 10μm, 115μm, 120μm, 150μm, 200μm, 210μm or within the range formed by any two of the above values; the suitable pole piece total thickness T can be 120μm, 130μm, 140μm, 150μm, 155μm, 160μm, 165μm, 170μm, 175μm, 180μm, 185μm, 190μm, 195μm, 200μm, 250μm, 300μm, 350μm, 400μm, 420μm or within the range formed by any two of the above values.

[0069] In an optional embodiment, when the energy density is increased by increasing the thickness of the pole piece, the mechanical stability of the battery decreases and the safety performance decreases, and the content of the first ether solvent needs to be further increased to improve the safety performance. However, when the safety performance is improved, the excessive content of the first ether solvent will cause the thickening of the interface film, resulting in the SEI film becoming unstable, increasing the barrier to lithium ions, and resulting in reduced cycle performance. In the present invention, by further comprehensively controlling the A / T value, that is, controlling 0.03≤A / T≤0.5, preferably 0.1≤A / T≤0.4, the A / T is controlled to cooperate with the oxygen content of LiFSI, the second ether solvent (F-EFPE) and the first ether solvent in the electrolyte, and the purpose of synchronously and comprehensively improving the cycle performance and safety performance is achieved under the premise of ensuring the energy density.

[0070] As an example, the value of A / T may be 0.03, 0.05, 0.1, 0.2, 0.3, 0.4 or 0.5 or within a range formed by any two of the above values.

[0071] The positive electrode sheet includes a current collector and a positive electrode active material layer arranged on the surface of the current collector, the positive electrode active material layer includes 80% to 99.8% of high nickel ternary material, 0.1% to 10% of conductive agent, and 0.1% to 10% of binder; preferably, the positive electrode active material layer includes 90% to 99.6% of high nickel ternary material, 0.2% to 5% of conductive agent, and 0.2% to 5% of binder.

[0072] The present invention does not particularly limit the conductive agent in the positive electrode sheet, which can be selected from the conductive agents commonly used in the art, including but not limited to one or more of acetylene black, conductive carbon black, Ketjen black, conductive graphite, carbon nanotubes, conductive carbon fibers, and graphene;

[0073] The present invention does not particularly limit the binder in the positive electrode sheet, which can be selected from binders conventionally used in the art, including but not limited to one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyethylene oxide.

[0074] The negative electrode sheet of the present invention includes a current collector and a negative electrode active material layer disposed on the surface of the current collector. The negative electrode active material can be a negative electrode active material for lithium metal batteries known in the art. The active material of the negative electrode active material layer can be selected from at least one of lithium metal and lithium alloy. The current collector of the negative electrode sheet can be selected from high-strength copper foil in the art. The negative electrode active material layer also includes a conductive agent and a binder. The present invention does not specifically limit the types of conductive agents and binders in the negative electrode sheet. The selection range can refer to the types of conductive agents and binders in the positive electrode sheet, and will not be repeated here.

[0075] The negative electrode sheet of the present invention can be prepared by the following method: lithium alloy and copper foil of a certain thickness are selected, rolled under a certain pressure and then cut into pieces to obtain lithium metal negative electrode sheets, and then dried to obtain the negative electrode sheets.

[0076] The material and shape of the separator used in the lithium metal battery of the present application are not particularly limited, and may include any technology disclosed in the prior art.

[0077] The present invention does not specifically limit the preparation method of the lithium-ion battery, and the lithium-ion battery can be prepared by conventional preparation methods in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence, so that the separator is located between the positive electrode sheet and the negative electrode sheet, and the battery core is obtained through the stacking process, and then the lithium-ion battery of the present invention is obtained through the processes of baking, liquid injection, formation, packaging, etc.

[0078] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of protection claimed in the present application. In all examples and comparative examples of the present application, the unit wt% represents the mass percentage content.

[0079] Example 1

[0080] A lithium metal battery, the preparation process is as follows:

[0081] (1) Preparation of positive electrode sheet

[0082] The positive electrode active material (high nickel ternary material LiNi 0.8 Co 0.1Mn 0.1 O2+4000ppm of 1:1:1 coating elements Al+Mg+Zr), conductive agent carbon black, and binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone at a mass ratio of 96.5:2:1.5, and are fully stirred to form a uniform positive electrode slurry. The positive electrode slurry is coated on the safety primer, and after drying, rolling and cutting, a positive electrode sheet with a thickness of T1=85μm is obtained; the mass proportion D wt% of the single crystal material in the high nickel ternary material is 60wt%.

[0083] (2) Preparation of negative electrode sheet

[0084] The lithium metal was composited onto a 6 μm high-strength copper foil by physical rolling. After cutting and slitting, a negative electrode sheet with a total thickness of 100 μm was obtained. The negative electrode sheet was placed in a dry argon atmosphere glove box for storage. The surface density of the negative electrode sheet was 5 mAh / cm 2 .

[0085] (3) Preparation of electrolyte

[0086] As shown in Table 1, in a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), Awt% of the first ether solvent and Bwt% of F-EFPE are mixed evenly to obtain an electrolyte solvent, and the type of the first ether solvent is shown in Table 1; wherein Formula 1-1 is ethylene glycol diethyl ether, and the oxygen content is A'wt% which is 27wt%; wherein Formula 1-9 is butyl 2-methoxyethyl ether, and the oxygen content is A'wt% which is 24wt%; wherein Formula 1-10 is ethylene glycol formate ethyl ether, and the oxygen content is A'wt% which is 30wt%; then Cwt% of lithium bis(fluorosulfonyl)imide (LiFSI) is added to the electrolyte solvent, and after dissolution, Fwt% of the flame retardant additive is added and stirred evenly, as shown in Table 1 below.

[0087] Table 1

[0088]

[0089] The above raw materials are mixed and tested for moisture and free acid to obtain an electrolyte.

[0090] (4) Diaphragm

[0091] PE porous polymer film is used as the isolation membrane.

[0092] (5) Battery assembly

[0093] The positive electrode sheet, negative electrode sheet and separator prepared above are stacked in order so that the separator is located between the positive electrode sheet and the negative electrode sheet, and then the electrode ears are welded and the sheets are stacked to obtain a battery cell. In this embodiment, the energy density of the battery cell is controlled to be at the same level. After the battery cell is placed in an aluminum-plastic film packaging bag, a lithium-ion battery is prepared through processes such as liquid injection, formation, secondary sealing, and sorting.

[0094] Example 2

[0095] A lithium metal battery. The difference between this embodiment and embodiment 1-1 is that the type of high-nickel ternary material in the positive electrode sheet, the coating element content, and the content D wt% of the single crystal material are set differently. The parameter settings are shown in Table 2 below.

[0096] Table 2

[0097] Single crystal D wt% High nickel ternary material Type of coating element Coating element content ppm B / D Example 2-1 60 <![CDATA[LiNi 0.6 What 0.2 Mn 0.2 O2]]> 1:1:1 Al:Mg:Zr 4000 0.72 Example 2-2 60 <![CDATA[LiNi 0.8 What 0.1 Mn 0.1 O2]]> 1:1:1 Al:Mg:Zr 100 0.72 Example 2-3 60 <![CDATA[LiNi 0.8 What 0.1 Mn 0.1 O2]]> 4:2:1 Al:Mg:Zr 7000 0.72 Embodiment 2-4 50 <![CDATA[LiNi 0.8 What 0.1 Mn 0.1 O2]]> 3:1:1 Al:Mg:Zr 4000 0.86 Embodiment 2-5 70 <![CDATA[LiNi 0.8 What 0.1 Mn 0.1 O2]]> 1:1:1 Al:Mg:Zr 4000 0.62 Embodiment 2-6 80 <![CDATA[LiNi 0.8 What 0.1 Mn 0.1 O2]]> 1:1:1 Al:Mg:Zr 4000 0.54 Embodiment 2-7 15 <![CDATA[LiNi 0.8 What 0.1 Mn 0.1 O2]]> 1:1:1 Al:Mg:Zr 4000 2.88 Embodiment 2-8 10 <![CDATA[LiNi 0.8 What 0.1 Mn 0.1 O2]]> 1:1:1 Al:Mg:Zr 4000 4.32

[0098] The other parameter settings of this embodiment are the same as those of Embodiment 1-1.

[0099] Example 3

[0100] A lithium metal battery, the difference between each embodiment and embodiment 1-1 is that the negative electrode sheet thickness T1, the positive electrode sheet thickness T2, and the total electrode sheet thickness T are set differently, and the parameter settings are shown in Table 3 below.

[0101] Table 3

[0102] T1 T2 T A / T Example 3-1 80 105 185 0.156 Example 3-2 90 110 200 0.144 Example 3-3 100 115 215 0.134 Embodiment 3-4 80 80 160 0.180

[0103] The other parameter settings of this embodiment are the same as those of Embodiment 1-1.

[0104] Example 4

[0105] A lithium metal battery, each embodiment differs from embodiments 1-3 in that the thickness T1 of the negative electrode sheet, the thickness T2 of the positive electrode sheet, and the total thickness T of the electrode sheet are set differently, and the parameter settings are shown in Table 4 below.

[0106] Table 4

[0107]

[0108]

[0109] The other parameter settings of this embodiment are the same as those of embodiments 1-3.

[0110] Comparative Example 1

[0111] A lithium metal battery, which differs from Example 1-1 in that the second ether solvent (F-EFPE) is replaced by propyl propionate PP, and other parameter settings are the same as those of Example 1-1.

[0112] Comparative Example 2

[0113] A lithium metal battery, which differs from Example 1-1 in that LiFSI is replaced by lithium hexafluorophosphate (LiPF6), and other parameter settings are the same as those of Example 1-1.

[0114] Comparative Example 3

[0115] A lithium metal battery, which differs from Example 1-1 in that ethylene glycol diethyl ether is replaced by isobutyl ether, and its oxygen content A'wt% is 16wt%, and other parameter settings are the same as those of Example 1-1.

[0116] Experimental example

[0117] The lithium-ion batteries obtained in the examples and comparative examples were subjected to room temperature cycle performance tests, low temperature cycle performance tests, energy density tests, and overcharge tests, respectively.

[0118] 1. Low temperature cycle performance test:

[0119] The battery obtained in the embodiment and the comparative example was discharged to 3V at 0.2C, and after standing for 5 minutes, the lithium-ion battery was placed in a 5°C environment, stood for 4 hours, and charged to the upper limit voltage (4.25V) at 0.3C constant current, stood for 5 minutes, and then discharged to 3.0V at 0.5C constant current, and stood for 5 minutes. This is a charge and discharge cycle; the charge and discharge cycle is 100 times. The highest discharge capacity of the first three cycles is recorded as the initial capacity Q0, and the discharge capacity of the 100th cycle is Q1. The capacity retention rate of the battery is calculated as Q1 / Q0×100%.

[0120] 2. Normal temperature cycle performance test:

[0121] The battery obtained in the embodiment and the comparative example was placed in an environment of 25±2℃, charged to the upper limit voltage (4.25V) at 0.7C constant current, then charged to 0.05C at 4.25V constant voltage, and left to stand for 5 minutes; then discharged to 3.0V at 0.5C constant current, and left to stand for 5 minutes, which is one charge and discharge cycle; the charge and discharge cycle was repeated 500 times. The highest discharge capacity of the first three cycles was recorded as the initial capacity Q2, and the discharge capacity of the 500th cycle was recorded as Q3. The capacity retention rate of the battery was calculated as Q3 / Q2×100%.

[0122] 3. Energy density test:

[0123] The batteries obtained in the examples and comparative examples were charged to an upper limit voltage of 4.255 V at 25°C ± 2°C, and then discharged to a lower limit voltage of 3.0 V at 0.2C. The discharge energy was recorded as ED. The energy density of the lithium-ion battery was then calculated using the following formula: Energy density = ED / (length × width × height of the lithium-ion battery).

[0124] 4. Overcharge test:

[0125] The batteries obtained in the examples and comparative examples were discharged at 0.2C to a cut-off voltage of 3.0V at 25°C±2°C and allowed to stand for 5 min. They were then charged at 2C constant current to 4.8V and at 4.8V constant voltage for 7 h. The battery appearance was observed to see if it was bulging or catching fire or exploding.

[0126] The experimental results corresponding to the above embodiments 1-3 are shown in the following tables 5-8.

[0127] Table 5

[0128] Normal temperature cycle / % Low temperature cycle / % Energy densityWh / L Overcharge test Example 1-1 90.2 92.5 768 10 / 10 Example 1-2 86.5 89.2 767 8 / 10 Examples 1-3 89.1 91.4 767 9 / 10 Examples 1-4 89.2 91.3 768 8 / 10 Examples 1-5 88.4 89.7 767 9 / 10 Examples 1-6 87.1 86.3 766 8 / 10 Examples 1-7 87.3 86.5 766 6 / 10 Examples 1-8 88.6 87.3 767 9 / 10 Examples 1-9 88.4 87.1 767 10 / 10 Examples 1-10 85.5 86.2 767 8 / 10 Embodiment 1-11 90 91.2 768 10 / 10 Examples 1-12 90.1 91.1 768 10 / 10 Examples 1-13 89.9 91.5 767 10 / 10 Examples 1-14 89.7 91.3 767 10 / 10 Comparative Example 1 83.1 80.2 766 6 / 10 Comparative Example 2 83.9 81.6 766 4 / 10 Comparative Example 3 83.8 82.9 768 5 / 10

[0129] Table 6

[0130] Normal temperature cycle / % Low temperature cycle / % Energy densityWh / L Overcharge test Example 2-1 89.1 91.3 760 8 / 10 Example 2-2 88.3 90.1 765 9 / 10 Example 2-3 88.9 89.5 767 10 / 10 Embodiment 2-4 89.2 91.5 768 10 / 10 Embodiment 2-5 87.9 88.4 768 10 / 10 Embodiment 2-6 86.7 87.1 769 10 / 10 Embodiment 2-7 84.2 85.4 768 8 / 10 Embodiment 2-8 83.4 83.5 768 6 / 10

[0131] Table 7

[0132] Normal temperature cycle / % Low temperature cycle / % Energy densityWh / L Overcharge test Example 3-1 89.9 91.3 769 10 / 10 Example 3-2 89.1 90.2 770 9 / 10 Example 3-3 89.1 89.4 767 9 / 10 Embodiment 3-4 88.9 90.1 763 10 / 10

[0133] Table 8

[0134] Normal temperature cycle / % Low temperature cycle / % Energy densityWh / L Overcharge test Example 4-1 88.5 89.1 770 8 / 10 Example 4-2 88.9 89.6 769 9 / 10 Example 4-3 89 89.5 769 9 / 10 Example 4-4 88.8 89.3 768 9 / 10 Embodiment 4-5 88.1 89.1 767 9 / 10 Embodiment 4-6 86.7 87.4 766 7 / 10

[0135] By comparing the data of Example 1 with the data of Comparative Examples 1 and 2, it can be seen that the present invention can take into account both low-temperature cycle stability and safety while ensuring high energy density, especially improving low-temperature cycle stability, by coordinating the second ether solvent in the specific content range of 20-65wt% with the first ether solvent with a specific oxygen content of A'≥18.

[0136] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention of this application.

Claims

1. A lithium metal battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The positive electrode sheet includes a high-nickel ternary material; The electrolyte includes a first ether solvent, a second ether solvent and lithium bis(fluorosulfonyl)imide; the oxygen content of the first ether solvent is A'wt%, A'≥18; the second ether solvent is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether; The mass proportion of the 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether in the electrolyte is Bwt%, and B is 9-65.

2. The lithium metal battery according to claim 1, characterized in that The structural formula of the first ether solvent is shown in Formula 1, Formula 1: wherein R1 and R2 are each independently selected from one or more of halogen, substituted or unsubstituted alkyl or ether having 1 to 5 carbon atoms, substituted or unsubstituted carboxylate having 2 to 5 carbon atoms, substituted or unsubstituted sulfonate having 1 to 5 carbon atoms, substituted or unsubstituted sulfate having 1 to 5 carbon atoms, and the total number of oxygen atoms in R1 and R2 is greater than or equal to 2; Preferably, the first ether solvent comprises at least one of the following structural formulas 1-1 to 1-8:

3. The lithium metal battery according to claim 1 or 2, characterized in that: The mass proportion of the first ether solvent in the electrolyte is Awt%, wherein A is 15-50; And / or, the mass proportion of the lithium bis(fluorosulfonyl)imide in the electrolyte is Cwt%, and C is 20-40; Preferably, A+B+C≥80.

4. The lithium metal battery according to any one of claims 1 to 3, characterized in that: The electrolyte also includes a flame retardant additive, and the flame retardant additive includes a phosphorus-containing compound; Preferably, the flame retardant additive is added in an amount of Fwt% of the electrolyte mass, 0.2≤F≤20; Preferably, the phosphorus-containing compound includes at least one of tris(2,2,2-trifluoroethyl) phosphate, ethoxy(pentafluoro)cyclotriphosphazene, p-toluoyl phosphate, trimethyl phosphate, ethyl hexafluorophosphate, propyl pentafluorophosphate, di(2,2,2-trifluoroethyl) carbonate, hexafluorocyclotriphosphazene, tricyanophosphate, tris(trimethylsilane) phosphate, and tris(trimethylsilane) phosphite.

5. The lithium metal battery according to any one of claims 1 to 4, characterized in that: The high-nickel ternary material includes single crystal material and / or polycrystalline material; Preferably, the mass percentage of the single crystal material to the high-nickel ternary material is D wt%, where D is 15-80, preferably 50-80.

6. The lithium metal battery according to claim 5, characterized in that 0.3≤B / D≤3, preferably, 0.4≤B / D≤1.

8.

7. The lithium metal battery according to any one of claims 1 to 6, characterized in that: The high-nickel ternary material includes doping elements, preferably, the doping elements are one or more elements selected from the group consisting of Al, Zr, Mg, Y, Ti, B, Sr, W, Si, La, and Nb; Preferably, the doping element includes at least one of Al, Mg and Zr; Preferably, based on the high-nickel ternary material, the content of the doping element is 100-7000 ppm.

8. The lithium metal battery according to any one of claims 1 to 7, characterized in that: The lithium metal battery is a laminated battery, the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes lithium metal.

9. The lithium metal battery according to claim 8, characterized in that The thickness of the negative electrode sheet is T1, the thickness of the positive electrode sheet is T2, the total thickness of the electrode sheets is T, T=T1+T2, 0.03≤A / T≤0.5, preferably, 0.1≤A / T≤0.

4.

10. The lithium metal battery according to claim 9, characterized in that 40μm≤T1≤210μm, 50μm≤T2≤210μm, 120μm≤T≤420μm.